FROM THE HISTORY OF THE FORMATION OF THE PERIODICAL PRESS (International Conference on Modern Science and Scientific Studies, 2025)
This article provides a comprehensive analysis of the history of the formation of the periodical press from ancient times to its development in Uzbekistan. It covers global processes, from the first methods of transmitting information in ancient Rome to the role of Johannes Gutenberg's invention of the printing press in the development of the press, to the emergence of the first newspapers and magazines in the 17th century. The article also examines in detail the formation of the periodical press in Uzbekistan, in particular, the early publications such as "Turkestanskiye Vedomosti" and the modern press, including the "Taraqqi" newspaper, its role in the national revival, and its changes during the Soviet and independent periods. The article reveals the importance of the periodical press in socio-political, economic and cultural development.